Pelatihan Pembuatan Produk Jamur Tiram Sebagai Upaya Untuk Meningkatkan Pendapatan Ibu-Ibu PKK Paaraman Kelurahan Dawuhan Kabupaten Situbondo - Nurul Avidhah Elhany; Desi Indriyani; Creani Handayani; Shinta Nuriya Prayudi; Dinda Mulyasari; Gilang Saputra (GUNAVATTA : Jurnal Pengabdian Masyarakat, 2025)
Oyster Mushroom is one type of mushroom that has now become a popular choice for healthy food. In addition to being delicious and nutritious, oyster mushrooms also have great market potential. The nutritional content of oyster mushrooms includes 27% protein, 1.6% fat, 58% carbohydrates, and 13.4% fiber. Oyster mushrooms not only offer a delightful taste but are also highly nutritious, as they contain plant-based protein and nearly complete amino acids, including essential amino acids that are important for the human body.This community service activity aimed to provide training for the PKK women group in Paaraman Dawuhan Situbondo. The women’s empowerment initiative through oyster mushroom processing training is beneficial in providing skills and fostering self-reliance among women, as well as increasing the market value of their products, thereby potentially boosting women's income. The community service activity was held in Paaraman, on May 8, 2025. The participants consisted of 30 members of the PKK Paaraman group. The activity was carried out through educational sessions using counseling and hands-on training methods. From the results of this activity, it can be concluded that mushrooms have greater potential when processed into various value-added products. Processed mushroom products offer opportunities for the PKK Paaraman women to increase the market value of oyster mushrooms. The training provided knowledge on how to explore business opportunities through oyster mushroom products, particularly white oyster mushrooms, including the production of crispy mushrooms and mushroom satay. This effort can help improve household income and the local economy in the Paaraman Dawuhan Situbondo.